2018
DOI: 10.4103/tjo.tjo_44_17
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting surgical outcome of intermittent exotropia

Abstract: PURPOSE:The purpose of this study was to investigate the factors affecting surgical outcome in intermittent exotropia.DESIGNS:This was a retrospective interventional study.METHODS:Intermittent exotropic patients who had undergone surgical correction with a postoperative follow-up period of 1 month or more were included in the study. Surgical success was defined as an alignment between 10 prism diopters (PD) of exotropia or 5 PD of esotropia at 1 month. After data collection, data were analyzed in SPSS version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This is inconsistent with our results. A large number of studies have shown that the recovery of binocular visual function after strabismus correction is related to many factors, such as the patient's operation age, [29][30][31][32][33][34][35] strabismus type, [32,36] and preoperative strabismus degree. [33] The younger the operation age and the smaller the preoperative strabismus degree, the better the recovery of binocular visual function after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is inconsistent with our results. A large number of studies have shown that the recovery of binocular visual function after strabismus correction is related to many factors, such as the patient's operation age, [29][30][31][32][33][34][35] strabismus type, [32,36] and preoperative strabismus degree. [33] The younger the operation age and the smaller the preoperative strabismus degree, the better the recovery of binocular visual function after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The logarithm of the minimum angle of resolution BCVA in the 2 groups was 0 (0-0.0) and 0 (0-0) with no significant difference (Z = −1.462, P = .144). The mean preoperative strabismus degree at 33 cm and 6 m accommodative targets in the IXT group was35.5 (30-45) and 30 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), respectively. The mean postoperative strabismus degrees measured at 33 cm and 6 m accommodative targets in the IXT group were −3 (−6−0) and −2 (−6-), respectively.…”
Section: Baseline Characteristics Of the 2 Groupsmentioning
confidence: 99%